GLOBAL CIVIL SOCIETY AND HUMANITARIAN CRISES: HOW WANEP PLAYS ITS ROLE IN WEST AFRICA IN 2019 - Abd Azis; Muhammad Fadilah Aziz; Mutiarah Azizah Dyah Pramesti; Herdiani Narita; Novita Putri Rudiany; Indra Kusumawardhana (Journal of Social Political Sciences, 2023)
Many reports in the mass media regarding the humanitarian crisis caused by economic and political instability in West Africa continued to become headlines that were widely discussed throughout 2019. The saying "there will be no smoke if there is no fire" also applies to the situation in West Africa. This crisis happened due to several reasons such as the increase in armed conflict crises, civil war, authoritarian leaders, and rebellions carried out by extremist groups. Instead of offering significant solutions to end the crisis, the government as a key actor sometimes even becomes the root cause of the conflict. Consequently, the situation triggered several civil society grassroots movements in various countries in West Africa. One of the global civil society movements that later emerged was The West Africa Network for Peacebuilding (WANEP). This research aims to look further at how WANEP worked in responding to the instability in West Africa in 2019. In looking at the role of WANEP, the Neo Kantian approach is used as the basis perspective in understanding the global civil society movements in peacebuilding attempts. The method used in this study is a qualitative method by analyzing data sources from official reports and previous studies, which are relevant to answering the research question. It is found that WANEP had initiated and was involved in many capacity-building efforts to educate the people and minimize the impacts of the crisis.